Fake news, propaganda, and plain old lies how to find trustworthy information in the digital age - Barclay, Donald A. (Lanham, Maryland Rowman & Littlefield, an imprint of the Rowman & Littlefield Publishing Group, Inc., 2018)
Fake News, Propaganda, and Plain Old Lies explains how to identify deceptive information and seek out the most trustworthy information to inform decision making in your personal, academic, professional, and civic lives. Barclay takes an objective, non-partisan approach to the topic of sorting deceptive information from trustworthy information.
Credible information: why it matters, what are its limitations -- Fake news as phenomenon: (almost) nothing new under the sun -- Tricks of the trade: techniques that lower your information guard -- Logical fallacies: more tools of deception -- Evaluating an information source: nine essential questions everyone should ask -- Power in numbers: negotiating the statistics minefield -- Scholarly information: identifying, evaluating, and understanding it -- Help is where you find it: resources for evaluating information -- Final thoughts.
Includes bibliographical references (pages 199-211) and index.
Keywords: Fake news; Journalism -- History -- 21st century; Online journalism